2006
DOI: 10.1128/jvi.02642-05
|View full text |Cite
|
Sign up to set email alerts
|

LC16m8, a Highly Attenuated Vaccinia Virus Vaccine Lacking Expression of the Membrane Protein B5R, Protects Monkeys from Monkeypox

Abstract: The potential threat of smallpox as a bioweapon has led to the production and stockpiling of smallpox vaccine in some countries. Human monkeypox, a rare but important viral zoonosis endemic to central and western Africa, has recently emerged in the United States. Thus, even though smallpox has been eradicated, a vaccinia virus vaccine that can induce protective immunity against smallpox and monkeypox is still invaluable. The ability of the highly attenuated vaccinia virus vaccine strain LC16m8, with a mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 34 publications
3
110
0
Order By: Relevance
“…Satellite lesions appeared with Lister but not with LC16m8. Similarly, on day 28, the pigmentation of the scars was apparent with Lister, but not with LC16m8 [28]. These studies indicated that LC16m8, a highly attenuated virus, would be much safer with minimum escape.…”
Section: Vaccine Strain Vis-à-vis Escape Of Vaccine Virusmentioning
confidence: 82%
“…Satellite lesions appeared with Lister but not with LC16m8. Similarly, on day 28, the pigmentation of the scars was apparent with Lister, but not with LC16m8 [28]. These studies indicated that LC16m8, a highly attenuated virus, would be much safer with minimum escape.…”
Section: Vaccine Strain Vis-à-vis Escape Of Vaccine Virusmentioning
confidence: 82%
“…In addition to employing a non-physiological route of infection, another major drawback in established NHP models is that the virus has to be administered in very high doses to induce a severe or fatal disease. At least 10 6 pfu of MPXV must be injected SC to induce a lethal infection in cynomolgus macaques (Saijo et al, 2006), and IV inoculation of at least 5 × 10 7 pfu of MPXV led to a fatal infection in cynomolgus and rhesus macaques ( [Earl et al, 2004] and [Hooper et al, 2004]). The three inoculation routes established for the MPXV macaque model that come closest to the natural route of smallpox infection were IT ( [Stittelaar et al, 2005] and [Stittelaar et al, 2006]), aerosolized (Zaucha et al, 2001) and IN administration of MPXV (Marriott, 2008).Even so, very high doses of 10 7 pfu are needed to induce a severe or lethal infection.…”
Section: Discussionmentioning
confidence: 99%
“…6 pfu results in a milder course of disease, which most animals survive ( [Zaucha et al, 2001], [Hooper et al, 2004], [Stittelaar et al, 2005], [Stittelaar et al, 2006] and [Saijo et al, 2006]). Additionally, working with MPXV and VARV is technically challenging, as it requires biosafety level 3 or 4 laboratories, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…While the current licensed live vaccinia virus-based vaccine is extremely effective [3] and results in remarkably long-lived immune responses (e.g., [4]), it has an unacceptable safety profile [5,6] for wide use when considered in today's setting of global eradication of active smallpox disease. Approaches to develop safer smallpox vaccines have ranged from the study of more attenuated live vaccinia viruses (such as MVA [7][8][9] or LC16m8 [10,11]) to subunit vaccines that rely on specific viral targets delivered either as DNA plasmids [12][13][14][15] or purified proteins [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%